Analisis Kritis Ketidakselarasan Pesan dan Perilaku Penceramah Online Gen Z dalam Perspektif Pendidikan Islam - Ardini, Fhina; Amalia, Niesa; Ramadhan, Viona Putri; Syaputra, Adrian; Rizqa, Miftahir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the inconsistency between the messages and behaviors of online preachers from Generation Z within the perspective of Islamic education. In the digital era, social media platforms such as TikTok, YouTube, and Instagram have become primary spaces for modern da’wah that are interactive and appealing to younger audiences. However, this advancement also presents significant challenges, particularly the dissonance between the Islamic values conveyed and the preacher’s actual behavior in the public sphere. This research employs a library research method by analyzing theories of communication, digital media, and Islamic education. The findings indicate that the main factors contributing to this inconsistency include algorithmic pressure from social media, commercialization of da’wah, lack of religious mentorship, and the digital culture of Gen Z that prioritizes popularity. From the standpoint of Islamic education, this phenomenon underscores the importance of integrating digital literacy, online preaching ethics, and character formation into both formal and non-formal educational curricula. Therefore, this study recommends strengthening the role of Islamic educational institutions in guiding young preachers so that digital da’wah remains ethical, educational, and truly reflective of authentic Islamic moral and spiritual values.